LITERATURE AS A REFLECTION OF SOCIETAL CHANGE: THEMES OF IDENTITY AND BELONGING - Mundafale, Aachal (International Journal of Research -GRANTHAALAYAH, 2017)
Literature has always been a way for people to see how society changes, fights, hopes, and worries. For hundreds of years, writers have written about political revolutions, colonial encounters, migrations, industrialization, globalization, and changes in technology. By doing this, they have shed light on how ideas of identity and belonging are changing. Literature illustrates how individuals navigate their positions within evolving social structures, from the emergence of the modern nation-state to current discussions concerning gender, race, and diaspora. This article examines the ways in which literature mirrors societal transformation through persistent themes of identity and belonging across various historical epochs and cultural settings.